Pure Red Cell Aplasia with Del(20q) Sensitive for Immunosuppressive Treatment - Anh Khoi Vo; Hilde Kollsete Gjelberg; Randi Hovland; Marte Karen Lindstad Brattås; Øystein Bruserud; Håkon Reikvam (Case Reports in Hematology)
Pure red cell aplasia (PRCA) is a rare syndrome that only affects the erythroid lineage. It is defined by a normocytic, normochromic anemia with a marked reticulocytopenia and severe reduction or absence of erythroid precursors in the bone marrow. Treatment of primary, idiopathic PRCA is immunosuppressive therapy. Although it is rare, isolated cytogenetic abnormalities can be seen in PRCA, and abnormal karyotype is associated with poor response to immunosuppressive therapy and poor prognosis. We describe a 77-year-old male with primary, idiopathic PRCA and a deletion of chromosome 20q, del(20q), in the bone marrow cells. He was successfully treated with immunosuppressive therapy and became transfusion-independent. The same cytogenetic abnormality has also been described in a few other reports; taken together, these observations suggest that del(20q) may represent a recurrent cytogenetic abnormality in PRCA. Our case report clearly illustrates that even patients with primary PRCA and an abnormal karyotype can respond to immunosuppression and become transfusion-independent.